Method for producing carbon material granules

JP7633480B1Active Publication Date: 2025-02-20DR GOO

Patent Information

Application Number
JP2024008979
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-01-24
Publication Date
2025-02-20
Estimated Expiration
2044-01-24

AI Technical Summary

Benefits of technology

【0010】 本発明の一態様によれば、金属不純物を低減でき、かつ、分散性に優れているカーボン材料造粒物、並びに、カーボン材料造粒物の製造方法を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007633480000002
    Figure 0007633480000002
  • Figure 0007633480000003
    Figure 0007633480000003
  • Figure 0007633480000001
    Figure 0007633480000001
Patent Text Reader

Abstract

To provide a carbon material granule capable of reducing metal impurities and having excellent dispersibility. The present invention relates to a carbon nanotube composition comprising: carbon black having a particle size of 500 μm or less as measured by the method described in JIS K-6219-4; carbon nanotubes that satisfy either one of the following conditions 1 and 2; and a solvent-soluble polymer attached to the carbon black and the carbon nanotubes. Carbon material granules. (Condition 1) Carbon nanotubes that have been subjected to a graphitization treatment and then a crushing treatment, and the particle size of the carbon nanotubes is 50 is less than 100 μm. (Condition 2) The carbon nanotubes, which are either powder or granular carbon nanotubes, are subjected to a pulverization process and then graphitized.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a carbon material granule and a method for producing the carbon material granule. [Background technology]

[0002] Lithium-ion secondary batteries (hereinafter sometimes referred to as Lib) are used in mobile phones, laptops, digital cameras, and automobiles (e.g. EV, HEV, P-HEV), and have made a great contribution to improving the productivity of various industries and the quality of life. The electrodes of Lib are formed from a positive electrode in which an electrode mixture consisting of a positive electrode active material containing lithium ions, a conductive additive, and an organic binder is fixed to a metal foil collector, and a negative electrode in which an electrode mixture consisting of a negative electrode material capable of inserting and removing lithium ions, a conductive additive, and an organic binder is fixed to the surface of a metal foil assembly.

[0003] Usually, lithium transition metal composite oxides such as lithium cobalt oxide are used as the positive electrode material, but these have low electronic conductivity and sufficient battery performance cannot be obtained when used alone. Therefore, carbon black (hereinafter sometimes referred to as CB), especially acetylene black or ketjen black, is added as a conductive additive to improve the conductivity and reduce the internal resistance of the electrode. However, the Lib industry and its users are demanding even higher performance products, such as higher capacity, improved safety, and reduced cycle degradation caused by repeated charging and discharging.

[0004] As one of the measures to meet this demand, in addition to the means of blending carbon nanotubes (hereinafter sometimes referred to as CNTs) with conventional CB as a conductive additive, particularly for the positive electrode, or using CNTs alone, attempts are also being made to improve the situation by using a granulated material that is made by uniformly blending CB and CNTs and then adding a polymer.

[0005] There is a method for producing carbon material granules (see Patent Document 1), which includes the steps of dry-grinding and mixing CB granules and CNT granules so as to satisfy specified conditions to obtain a mixture, dissolving a specific solvent-soluble polymer in a solvent to prepare a binder solution, and adding a specified amount of the binder solution to the mixture while mixing and granulating to obtain carbon material granules.

[0006] When CNTs containing metal impurities are used as a conductive additive for the positive electrode, the positive electrode is in an oxidizing atmosphere, so transition metals such as iron or cobalt may be oxidized and dissolved. In addition, when CNTs containing metal impurities are used for the negative electrode, metal deposition may occur. In the worst case, the eluted or precipitated metal may break the separator membrane, resulting in an internal short circuit. Furthermore, even if these metal impurities are initially tiny, the deposits may grow large and break the separator as the battery is used. In order to create a safe LIB that is free of internal short circuits and does not cause partial heat generation or deterioration, it has become important to reduce the metal impurities of the CNTs used as conductive additives as much as possible and to use CNTs with excellent dispersibility. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Patent No. 7126666 Summary of the Invention [Problem to be solved by the invention]

[0008] An object of the present invention is to provide a carbon material granule that can reduce metal impurities and has excellent dispersibility, and a method for producing the carbon material granule. [Means for solving the problem]

[0009] According to the present invention, there are provided a carbon material granule and a method for producing a carbon material granule, which are described below. [1] A carbon black having a particle size of 500 μm or less as measured by the method described in JIS K-6219-4, carbon nanotubes satisfying either one of the following conditions 1 and 2, and a solvent-soluble polymer attached to the carbon black and the carbon nanotubes, Carbon material granules. (Condition 1) Carbon nanotubes that have been subjected to a graphitization treatment and then a crushing treatment, and the particle size of the carbon nanotubes is 50 is less than 100 μm. (Condition 2) The carbon nanotubes, which are either powder or granular carbon nanotubes, are subjected to a pulverization process and then graphitized. [2] The carbon material granule according to [1], The solvent-soluble polymer is a water-soluble polymer, The solvent is water. Carbon material granules. [3] A method for producing the carbon material granule according to [1] or [2], A step of mixing carbon black having a particle size of 500 μm or less according to the method described in JIS K-6219-4 with carbon nanotubes satisfying either one of the condition 1 and the condition 2 to obtain a mixture; dissolving the solvent-soluble polymer in a solvent to prepare a binder solution; and adding the binder solution little by little to the mixture, mixing the mixture, and granulating the mixture to obtain a carbon material granule. A method for producing carbon material granules. [4] A method for producing the carbon material granule according to [1] or [2], A step of mixing carbon black having a particle size of 500 μm or less according to the method described in JIS K-6219-4 with carbon nanotubes satisfying either one of the condition 1 and the condition 2 to obtain a mixture; dissolving the solvent-soluble polymer in a solvent to prepare a binder solution; mixing the mixture with the binder solution to obtain a wet mixture; and granulating the wet mixture to obtain a carbon material granule. A method for producing carbon material granules. Effect of the Invention

[0010] According to one aspect of the present invention, it is possible to provide a carbon material granule that can reduce metal impurities and has excellent dispersibility, and a method for producing the carbon material granule. [Brief description of the drawings]

[0011] [Figure 1] FIG. 2 is a conceptual diagram showing an example of an extrusion granulator used in the present embodiment. [Diagram 2] 1 is a photograph showing dispersibility in the resin compositions obtained in Example 1, Comparative Examples 1 and 2, and Reference Examples 1 to 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, an embodiment of the present invention will be described, but the present invention is not limited to the following embodiment. Hereinafter, the carbon material granules may be simply referred to as "granules".

[0013] [Carbon material granules] First, the carbon material granules according to this embodiment will be described. The granulated material according to this embodiment contains CB having a particle size equal to or smaller than a specific particle size, CNT satisfying specific conditions, and a solvent-soluble polymer attached to the CB and the CNT. The reason why the present embodiment can reduce metal impurities and obtain carbon material granules with excellent dispersibility is not necessarily clear, but the present inventors speculate as follows.

[0014] First, the reason why metal impurities can be reduced is that the CNTs have been graphitized. The graphitization is a heat treatment at a high temperature of, for example, 2000°C or higher, and this graphitization can remove metal impurities (catalytic metals) derived from the catalyst that are mixed in the CNTs. In contrast, other methods for removing metal impurities derived from the catalyst that are mixed in the CNTs include (i) a method in which the CNTs are immersed in an acidic solution containing at least one of sulfuric acid, hydrochloric acid, and hydrofluoric acid to dissolve and remove the metal, or (ii) a method in which the CNTs are irradiated with microwaves to convert the metal impurities into metal oxides that are inactive at the operating voltage of the secondary battery and are not dissolved in the electrolyte. Of these, the acid treatment method (i) leaves acid ions on the CNT surface even if heat treatment (less than 600°C) is performed after pickling, so there is a risk of corrosion of the positive electrode material, and it may also damage the CNTs and cause lattice defects. In addition, since the surface of the catalytic metal is covered with a graphite layer, the acid solution alone cannot completely dissolve and remove the catalytic metal because the graphite layer prevents the acid solution from reaching the catalytic metal. Furthermore, the microwave irradiation method (ii) above has the problem that the CNTs are oxidized, decreasing the electrical conductivity of the CNTs. In this way, the method of graphitizing CNTs is optimal as a method for removing metal impurities (catalytic metals) derived from catalysts that are mixed in with the CNTs.

[0015] On the other hand, when the CNT is graphitized, the crystallization of the CNT proceeds, and there is a problem that the dispersibility in the resin is reduced. However, in this embodiment, the CNT is pulverized before or after the graphitization to be fine powder, or the CNT that is already fine powder is graphitized. Then, by being made into fine powder in this way, the dispersibility of the CNT in the resin is improved. Therefore, the inventors speculate that the granulated material according to this embodiment can reduce metal impurities and has excellent dispersibility.

[0016] (Carbon Black) The CB used in this embodiment has a particle size of 500 μm or less according to the method described in JIS K-6219-4. The particle size distribution of CNTs is measured according to JIS K-6219-4 "Method of determining the size distribution of granulated particles." The measuring device is a classification method that uses stacked mesh sieves, and there are sonic vibration, low-tap, and electromagnetic types depending on how the vibration is applied. Manufacturers of sonic vibration types include Hatsuratsu Co., Ltd. and Seishin Enterprise Co., Ltd. In addition to the two companies mentioned above, manufacturers of low-tap machines include CMT Co., Ltd. and AS ONE Co., Ltd. Manufacturers of electromagnetic shaking sieve machines include Tsutsui Rikagakuhin Co., Ltd. As an example of a specific measurement method, in the case of the low-tap type made by CMT Co., Ltd., 4 to 6 stacked mesh sieves with a diameter of 200 mm are set on the low-tap. The types of mesh are usually a combination of 10 mesh (1000μm opening), 30 mesh (500μm), 60 mesh (250μm), and 100 mesh (150μm), but 86 mesh (2000μm) and 149 mesh (100μm) may also be added for measurement. In the measurement, a tray is attached to the bottom, 100g of granulated product is placed on the top mesh sieve, the lid is set, and the sieve is shaken for 1 minute under the conditions of shaking speed 290rpm, amplitude 28mm, and number of strokes 156t.pm. The granulated product that is stuck on the top and in the openings of each sieve is scraped off, the weight of the sieves is measured, and the particle size distribution is calculated. The value of the opening of the mesh with the smallest opening among all the meshes that have been passed through is the particle size of the crushed product. The preferred particle size after pulverization is preferably 10 μm to 500 μm, more preferably 25 μm to 250 μm, when viewed using a rotary tap classification method. If the particle size is larger than 500 μm, not only will the number of aggregates increase and dispersibility deteriorate, but the uniform mixing of CB and CNT will also deteriorate. In addition, processing to make the particle size smaller than 10 μm is not easy because it involves industrial-scale production, and even if it can be processed, it will take a long time and is not practical. In addition, this processing cuts the fibers of the CNT, which is undesirable because it will deteriorate the conductivity. Furthermore, when pulverizing after blending CB and CNT, the particle size is preferably about the same as that of the CNT.

[0017] Examples of CB include those obtained by thermal decomposition methods such as the thermal method or the acetylene decomposition method, incomplete combustion methods such as the oil furnace method, and those obtained by heavy oil gasification processes such as the Texas process, the Fazer process, and the Shell process. These may be used alone or in combination of two or more types. Specific examples include the #4000 and #5000 series manufactured by Tokai Carbon Co., Ltd., the #3000 series manufactured by Mitsubishi Chemical Corporation, FX, HS, Denka Black, etc. manufactured by Denka Co., Ltd., the Conductex series manufactured by Birla Carbon Co., Ltd., the Vulcan series and LITX series manufactured by Cabot Corporation, the ENSACO series and SuperP-Li series manufactured by Imerys GC Corporation, and Printex L manufactured by Orion Engineer Carbons.

[0018] (Carbon Nanotubes) The CNTs used in this embodiment satisfy either the following condition 1 or the following condition 2. (Condition 1) Carbon nanotubes that have been subjected to a graphitization treatment and then a crushing treatment, and the particle size of the carbon nanotubes is 50 is less than 100 μm. (Condition 2) The carbon nanotubes, which are either powder or granular carbon nanotubes, are subjected to a pulverization process and then graphitized.

[0019] (Graphitization treatment) The graphitization treatment in this embodiment is a heat treatment at a temperature of 2000° C. or higher and 3000° C. or lower in a non-oxidizing atmosphere. More specifically, the graphitization process is carried out by heating and holding the CNTs at 2000°C or higher in an oxygen-free atmosphere (for example, in a nitrogen stream, in a vacuum, or in carbon powder (also known as packing powder, and usually coke powder or CB is used)). In this case, the presence of oxygen in the atmosphere reduces the yield of CNTs obtained, so it is desirable to keep the oxygen concentration in the atmosphere at 1% by volume or less. When this graphitization process is carried out on a large scale, it is advantageous to use an Acheson-type electric furnace. On the other hand, when it is carried out on a small scale, a specified amount of CNTs can be filled into a graphite pipe, which is then embedded in carbon powder, and an alternating current is passed through both ends of the pipe. Thus, in the graphitization process, it is preferable to heat the CNT to 2000°C or more and 3000°C or less, more preferably to heat to 2500°C or more and 2900°C or less, and particularly preferably to heat to 2700°C or more and 2900°C or less. When heated in such a temperature range, the crystallites of the CNT are rearranged and the shape changes, the wire diameter becomes slightly smaller, but the crystallinity grows. In addition, the higher the processing temperature, the more the functional groups or metal impurities on the surface can be reduced. However, it is thought that the higher the processing temperature, the stronger the entanglement of the primary aggregates or secondary aggregates that existed in the CNT before graphitization becomes due to the heat treatment, and the worse the dispersibility when mixed with resins, etc.

[0020] (Crushing process) The pulverization process in this embodiment includes dry pulverization and wet pulverization, which can be used depending on the purpose. The reason why the dispersibility of the graphitized CNT decreases is believed to be that the complex and strong entanglement of the CNT fibers cannot be disentangled by a normal dispersing machine or dispersion method. In order to disentangle the strong entanglement, it is preferable to use a powerful pulverization means. In this embodiment, it is preferable to use dry grinding. In the case of dry grinding, the grinding machine to be used varies depending on the target particle size and particle size distribution. For example, when the target is fine grinding to tens of μm or less, a jet mill, a pin mill, a vibration ball mill, or a planetary mill is used. Among grinding machine manufacturers, examples of jet mill type grinding machine manufacturers include Seishin Enterprise Co., Ltd., Aisin Nanotechnologies Co., Ltd., and Earth Technica Co., Ltd. Furthermore, examples of pin mill manufacturers include Makino Sangyo Co., Ltd., Nishimura Machinery Manufacturing Co., Ltd., and Hosokawa Micron Co., Ltd. Furthermore, examples of impeller mill manufacturers include Seishin Enterprise Co., Ltd., and Earth Technica Co., Ltd.

[0021] (CNT particle size) The particle size D of CNTs that satisfies the above condition 1 50 The particle size D of the CNTs that satisfies the above condition 2 must be 100 μm or less. 50 is preferably 100 μm or less. The particle size distribution of CNTs is measured by the laser diffraction / scattering method defined in ISO13320. The measurement was performed using a Laser Micron Sizer LMS-3000 (manufactured by Seishin Enterprise Co., Ltd.). The measurable range of this device is 0.01 to 3500 μm. The aqueous dispersion medium was prepared by adding 0.05 g of polyoxyethylene alkyl ether (Kao Corporation, product name Emulgen 705) as a surfactant to 50 mL of pure water. For the measurement, 10 mg of CNTs were weighed into a 20 mL vial, 10 mL of aqueous dispersion medium was added, and the CNTs were dispersed for about 10 minutes using an ultrasonic disperser. The optical model of the measurement was set to the refractive index of 1.520 for CNTs and 1.333 for water, respectively, for the measurement. CNT optimum particle size D 50 is 10 μm or more and 100 μm or less, and preferably 10 μm or more and 50 μm or less. If it is larger than 50 μm, many aggregates will be present and dispersibility will be poor. In addition, a process to make it finer than 10 μm is a process to cut the CNT fibers, which is not preferable because it will deteriorate the conductivity.

[0022] (Raw material CNT) The fiber diameter of the CNTs used as raw materials is 0.3 nm, which is the maximum diameter that can be produced using current technology, but it can be thinner than 0.3 nm. As the fiber diameter increases beyond 50 nm, the electrical and mechanical properties tend to decrease, and as the fiber diameter increases beyond 100 nm, the advantage over CB or carbon nanofibers tends to disappear. Furthermore, in this embodiment, from the viewpoint of the CNTs efficiently forming a three-dimensional network, the fiber diameter of the CNTs is more preferably 3 nm or more and 50 nm or less, even more preferably 5 nm or more and 40 nm or less, and particularly preferably 10 nm or more and 30 nm or less. The fiber length of CNT is related to electrical conductivity, mechanical properties, or dispersibility. The fiber length of CNT is preferably 0.1 μm or more and 2000 μm or less, and more preferably 1 μm or more and 1000 μm or less. As the fiber length becomes smaller, there is a tendency that it becomes difficult to express electrical conductivity or mechanical properties, and as the fiber length becomes larger, the entanglement of the fibers becomes stronger, and not only does it increase the number of poorly dispersed lumps, but it also increases the number of fiber breaks during kneading and dispersion, which is undesirable. The aspect ratio of CNT is about 10 to 10,000. In addition, as the CNT, a structure in which a hexagonal mesh graphite sheet is formed into a cylindrical shape is preferably used. The CNT may be either a single-layer CNT or a multi-layer CNT, and can be selected according to the final purpose. In addition, there is no limitation regarding the manufacturing method of CNT. Examples of the manufacturing method of CNT include a pyrolysis method in which a carbon-containing gas is brought into contact with a catalyst, an arc discharge method in which an arc discharge is generated between carbon rods, a laser evaporation method in which a carbon target is irradiated with a laser, a CVD method in which a carbon source gas is reacted at high temperature in the presence of metal fine particles, and a HiPco method in which carbon monoxide is decomposed under high pressure. In addition, the CNT may be doped with metal atoms.

[0023] (CNT content) In the granulated product according to this embodiment, the amount of CNT is preferably 5% by mass or more and 40% by mass or less, and more preferably 10% by mass or more and 35% by mass or less, relative to 100% by mass of the total amount of CB and CNT. If the amount of CNTs is equal to or less than the upper limit, the dispersibility of CNTs can be further improved, and if the amount of CNTs is equal to or more than the lower limit, the electrical conductivity can be further improved.

[0024] (Solvent-soluble polymer) The solvent-soluble polymer used in this embodiment is attached to the CB and CNT. Carbon nanotubes are said to have safety problems due to poor workability caused by their low bulk density and environmental pollution caused by their scattering. In order to solve these problems, in this embodiment, a solvent-soluble polymer is attached to the CNT and CB.

[0025] As the solvent-soluble polymer, any polymer that dissolves in water, organic solvents, and mixtures thereof can be used. The solvent is water, organic solvents, and mixtures thereof, and water is the most preferred. When water is used as the solvent, the solvent-soluble polymer is a water-soluble polymer. Examples of the solvent-soluble polymer include polymer-based surfactants and high molecular weight polymers. Examples of the surfactant include anionic surfactants, cationic surfactants, nonionic surfactants, and amphoteric surfactants, etc. These may be used alone or in combination of two or more. Examples of the high molecular weight polymer include ether-based polymers (polyethylene glycol (polyethylene oxide) and polypropylene glycol, etc.), vinyl-based polymers (polyvinyl alcohol, polyvinyl acetate, and polyvinylpyrrolidone, etc.), acrylamide-based polymers (polyacrylamide, etc.), amine-based polymers (polyethyleneimine and polybutyleneimine, etc.), cellulose-based polymers (methylcellulose, ethylcellulose, carboxymethylcellulose, hydroxyethylcellulose, and hydroxypropylmethylcellulose, etc.), and starch-based polymers (oxidized starch and gelatin, etc.). These may be used alone or in combination of two or more. Among these, from the viewpoint of reducing scattering or improving dispersibility, it is more preferable to use glycol-based polymers, and it is particularly preferable to use polyethylene oxide.

[0026] In the granulated product of this embodiment, the amount of the solvent-soluble polymer is preferably 1 part by mass or more and 30 parts by mass or less, and more preferably 3 parts by mass or more and 15 parts by mass or less, per 100 parts by mass of the total amount of carbon black and carbon nanotubes.

[0027] [Method of manufacturing carbon material granules] Next, a method for producing a granulated product according to this embodiment will be described. Examples of the method for producing the granulated product according to this embodiment include the first production method and the second production method described below.

[0028] (First method for producing carbon material granules) The first method for producing a granulated material according to this embodiment includes a step of grinding and mixing CNT and CB granules, if necessary (grinding and mixing step), a step of dissolving a solvent-soluble polymer in a solvent to prepare a binder solution (solution preparation step), and a step of adding the binder solution little by little to the mixture of CB and CNT, mixing, and granulating to obtain a carbon material granulated material (granulated material preparation step). The granulated material according to the present embodiment can be produced by the first method for producing the granulated material according to the present embodiment. However, the method for producing the granulated material according to the present embodiment is not limited to the method for producing the granulated material according to the present embodiment. For example, in the grinding and mixing step, CNT granules and CB are used and ground, but the grinding process may be omitted by using equivalent CNT or CB after the grinding process.

[0029] (Crushing and mixing process) In the grinding and mixing step, the CB granules are ground to a specific particle size or less, and the CNTs are ground as necessary so as to satisfy the condition 1 or the condition 2, and then mixed to obtain a mixture. Here, the order of dry grinding and mixing is not particularly limited. (1) The CB granules and CNTs may be dry ground separately and then mixed, or (2) the CB granules and CNTs may be mixed and then dry ground. There are two types of pulverization methods, dry pulverization and wet pulverization, which are used according to the purpose. In the present invention, dry pulverization is used, but in the case of the dry method, the pulverizer used varies depending on the target particle size and particle size distribution. For example, (1) when the purpose is medium pulverization (10 mm or less), an impeller mill, a pin mill, or a roller mill is used, and (2) when the purpose is fine pulverization (several tens of μm or less), a jet mill, a ball mill, a vibration ball mill, or a planetary mill is used. Among the manufacturers of crushers, those that make jet mill type crushers include Seishin Enterprise Co., Ltd., Aisin Nano Technologies Co., Ltd., and Earth Technica Co., Ltd. Furthermore, those that make pin mills include Makino Sangyo Co., Ltd., Nishimura Machinery Works Co., Ltd., and Hosokawa Micron Co., Ltd. Furthermore, those that make impeller mills include Seishin Enterprise Co., Ltd. and Earth Technica Co., Ltd. Furthermore, those that make sanitary rotary type crushers include Aishin Sangyo Co., Ltd. and Tokuju Kosakusho Co., Ltd. Among these, those that can be inserted directly from the raw material hopper into a mixer or twin-screw extruder while crushing in a sealed state include the sanitary type crusher made by Aishin Sangyo Co., Ltd., and the Randel Mill (RM-1N type) made by Tokuju Kosakusho Co., Ltd.

[0030] (Solution preparation process) In the solution preparation step, a solvent-soluble polymer is dissolved in a solvent to prepare a binder solution. The solvent-soluble polymer and the solvent are as described above. The concentration of the solvent-soluble polymer in the binder solvent is preferably from 1% by mass to 10% by mass, and more preferably from 2% by mass to 5% by mass. If the concentration of the solvent-soluble polymer is equal to or higher than the lower limit, the solvent-soluble polymer can be attached to the carbon material more efficiently. On the other hand, if the concentration of the solvent-soluble polymer exceeds the upper limit, the polymer does not sufficiently penetrate into the carbon material, and the effect of expelling air present on the surface or in pores that is detrimental to the conductive performance decreases, which tends to result in a decrease in the conductivity. By adding the solvent-soluble polymer at the lowest possible concentration, the solvent-soluble polymer can more easily penetrate into the voids in the carbon material, enabling a uniform coating over the entire carbon material. In addition, by adding a surfactant to the binder solution, the binder solution can be more easily penetrated into the carbon material.

[0031] (Granule preparation process) In the granule preparation step, the binder solution is added little by little to the mixture of CB and CNT while being mixed to obtain carbon material granules. The mixing equipment used here can be broadly divided into batch and continuous types. Representative examples of the batch type include a Henschel type stirring mixer and a batch type Loedige mixer. An example of the continuous type is a twin-shaft pin mixer that mixes by rotating twin screws.

[0032] Examples of Henschel type mixers include the "High Speed ​​Mixer" series manufactured by EarthTechnica, the "SPG" series manufactured by Technopaudal, the "FM Mixer" manufactured by Nippon Coke & Engineering Co., Ltd., the "SMB" or "SM" series manufactured by Kawata, and the "VG" series manufactured by Powlex. There are various models of Loedige mixers, from the M20 to the M8000D, sold by Matsubo Co., Ltd. An example of the biaxial pin type is the "Dow Pelletizer" manufactured by Shin-Nichinan Co., Ltd.

[0033] In the case of continuous mixing in the granulation preparation process, the process is as follows, taking a pin-type mixer as an example. That is, a fixed amount of CNT and CB mixture is charged from an inlet into a device with a rotating body in operation, a binder solution is added and mixed from an inlet at the rear of the inlet, and the granulation is taken out from an outlet and dried in a drying process described later. The mixing performance is adjusted by the residence time in the device. The longer the residence time, the more spherical the mixture becomes. If the desired granulation is not obtained, the pin-type mixer may be increased to two stages in series for granulation. The rotation speed of the rotating body is preferably 500 rpm or more and 3000 rpm or less, and more preferably 1000 rpm or more and 2000 rpm or less.

[0034] On the other hand, when batch mixing is performed in the granulation preparation process, the process is as follows, taking a Henschel mixer as an example. That is, as in the case of the continuous type, a predetermined amount of pulverized carbon nanotube and carbon black powder is charged into the mixer, and then the mixture is stirred with a rotor, a binder solution is added little by little, and while checking the mixed state, a solvent is added, and when the desired granulation particle size is reached, the granulation is taken out and dried in a drying process described below. The rotation speed of the rotor is preferably 300 rpm or more and 2500 rpm or less, and more preferably 500 rpm or more and 2000 rpm or less.

[0035] After the granule preparation step, a step of drying the carbon material granules (drying step) is performed. Vacuum drying, hot air drying, and the like are used for drying. As the hot air dryer, a vibration / fluidized dryer, a fluidized dryer, a box dryer, and a dryer type dryer can be used. On the other hand, as the vacuum (reduced pressure) dryer, a vacuum tray type dryer, a reduced pressure outer mixer type dryer, and a box type dryer can be used.

[0036] The drying temperature is preferably a temperature at which the solvent-soluble polymer does not deteriorate, and therefore there is an optimum temperature or a maximum temperature depending on the type of solvent-soluble polymer, but generally, the temperature is preferably from 40° C. to 200° C., more preferably from 50° C. to 150° C., and particularly preferably from 60° C. to 100° C. The drying time depends on the drying temperature, but is usually from 1 hour to 20 hours, and preferably from 2 hours to 10 hours.

[0037] (Second method for producing carbon material granules) The second manufacturing method of the granulated material according to this embodiment includes a step of grinding and mixing the CNT and CB granules as necessary (grinding and mixing step), a step of dissolving a solvent-soluble polymer in a solvent to prepare a binder solution (solution preparation step), a step of adding the binder solution while mixing the CB and CNT to obtain a wet mixture (granulation precursor) (wet mixture preparation step), and a step of granulating the wet mixture to obtain a carbon material granulated material (granulation preparation step). The second manufacturing method is different from the first manufacturing method in the preparation step of preparing a granulated product. In the following description, differences from the first manufacturing method will be mainly described, and overlapping descriptions will be omitted or simplified.

[0038] (Crushing and mixing process) The grinding and mixing step is generally as described above. However, the CB and CNT can be mixed by feeding the pulverized material into a mixer granulator such as a Henschel mixer or a Loedige mixer and mixing while adding water in which the polymer is dissolved, or by feeding the material directly into a mixer granulator such as a Henschel mixer without pulverization and pulverizing it in the granulator by stirring at high speed without adding water in which the polymer is dissolved, and then adding water in which the polymer is dissolved to produce a wet mixture that serves as a granulation precursor.

[0039] (Solution preparation process) The solution preparation step is as described above.

[0040] (Wet mixture preparation process) In the mixture preparation step, the mixture obtained in the grinding and mixing step is mixed with the binder solution obtained in the solution preparation step to obtain a wet mixture. Here, the blending amount of the binder solution is preferably adjusted according to the blending amount of the solvent-soluble polymer, that is, the blending amount of the solvent-soluble polymer is preferably 0.01 parts by mass or more and 15 parts by mass or less, more preferably 0.1 parts by mass or more and 12 parts by mass or less, and particularly preferably 2 parts by mass or more and 10 parts by mass or less, relative to 100 parts by mass of the total blending amount of the carbon black and the carbon nanotubes.

[0041] In this embodiment, a shearing treatment for shearing the CB and CNT may be performed during or after the wet mixture preparation step. However, in this embodiment, the CB and CNT are sufficiently pulverized in the above-mentioned pulverizing and mixing step, so this shearing treatment is not necessarily required.

[0042] (Granule preparation process) In the granule preparation step, the wet mixture obtained in the wet mixture preparation step is granulated to obtain carbon material granules. Note that granulation of the wet mixture enables continuous granulation, and the production efficiency of the granules can be improved. Examples of the granulator used here include an extrusion granulator and a shear crushing granulator. Among these, from the viewpoint of production efficiency, it is particularly preferable to use an extrusion granulator (see FIG. 1, which is a model of the inside of an extrusion granulator). As shown in FIG. 1, the extrusion granulator is equipped with a screw case 1, a screw 2, an extract blade 3, a screen 4, and a screen holder 5. The mainstream of extrusion granulators is a screw type extrusion granulator, and there are single-shaft and double-shaft types. In addition, they are roughly divided into two types, a front extruder and a side extruder, depending on the installation position of the extrusion screen die. In the case of a single-shaft screw, the screen die is mostly installed at the front end of the granulation chamber. On the other hand, in the case of a double-shaft, the screen die is often installed on both sides of the granulation chamber. Comparing the characteristics of a single shaft and a double shaft, the extrusion pressure is stronger in a single shaft, so the granulated product can have a relatively large particle size and can also have a high hardness. Twin-screw extrusion granulators are good for small particle size products and have weak particle strength, but are excellent in production efficiency. Examples of screw-type extrusion granulators and their manufacturers include the Pelleter Double EXD type or Fine Luzer EXR type made by Dalton Co., Ltd., Granumaster made by Okawara Seisakusho Co., Ltd., and Extrude Mix EM made by Hosokawa Micron Co., Ltd. Examples of the shear crushing granulator include the Speed ​​Mill HM Series manufactured by Fuji Yakuhin Kikai Co., Ltd., and the Chopper Mill manufactured by Nippon Pneumatic Mfg. Co., Ltd.

[0043] After the granule preparation step, a step of drying the carbon material granules (drying step) may be carried out as necessary. The drying step is as described above.

[0044] [How to use carbon material granules] Next, a method for using the granulated product according to this embodiment will be described. The granulated material according to the present embodiment can reduce metal impurities and has excellent dispersibility, and therefore, using the granulated material according to the present embodiment, a carbon material-containing resin composition useful as a constituent material for lithium ion secondary batteries can be produced.

[0045] Examples of the resin include polyolefin resin, polyhalogenated olefin resin, polyester resin, polyamide resin, polyimide resin, polyether resin, polyvinyl resin, polystyrene resin, polyvinyl alcohol resin, polymethacrylate resin, polyurethane resin, polyepoxy resin, polyphenol resin, polyurea resin, and polyethersulfone resin. EXAMPLES

[0046] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the examples, "parts" and "%" are by weight unless otherwise specified.

[0047] [Preparation Example 1] A graphitization treatment device was prepared in which electrodes were attached to both ends of a hollow graphite pipe with an inner diameter of 4 cm and a length of 100 cm, and the pipe could be directly heated by passing an alternating current. In this graphitization treatment device, about 15 g of "K-Nanos-100T", a pelletized CNT granule (raw CNT) manufactured by Kumho Petrochemical Co., Ltd., was packed in a cylindrical graphite container with an inner diameter of 3 cm, an outer diameter of 3.5 cm, and a length of 10 cm, and then inserted into the graphite pipe at approximately the center, and nitrogen gas was introduced into the graphite pipe. Then, an alternating current was passed through the graphite pipe, and the pipe was subjected to a heat treatment (graphitization treatment) at a temperature of 2900°C for 30 minutes to produce graphitized CNT.

[0048] [Preparation Example 2] "K-Nanos-100T", a pelletized CNT granule (raw CNT) manufactured by Kumho Petrochemical Co., Ltd., was pulverized using a jet mill "PJM-80" manufactured by Nippon Pneumatic Co., Ltd. to produce a pulverized product of raw CNT.

[0049] [Preparation Example 3] The graphitized CNT obtained in Preparation Example 1 was pulverized using a jet mill "PJM-80" manufactured by Nippon Pneumatic Co., Ltd. to produce a pulverized product of graphitized CNT. The particle size distribution of the graphitized CNT crushed product was measured by the laser diffraction / scattering method specified in ISO 13320. The measurement was performed using a Laser Micron Sizer LMS-3000 (manufactured by Seishin Enterprise Co., Ltd.). From the obtained particle size distribution, the particle size D 50 The particle size of graphitized CNTs, D 50 was 35 μm.

[0050] [Reference examples 1~4] A resin composition was prepared by blending 2% of each of the CNTs listed below into polypropylene resin (Prime Polymer's "J229E") and mixing the mixture at 210°C and 100 rpm for 4 minutes using a Plastomill. Reference example 1: Raw material CNT Reference Example 2: Graphitized CNT obtained in Preparation Example 1 Reference Example 3: Crushed raw CNT obtained in Preparation Example 2 Reference Example 4: Crushed product of graphitized CNT obtained in Preparation Example 3

[0051] [Example 1 and Comparative Examples 1 to 2] (Preparation of carbon material granules) First, the carbon material and binder solution materials shown below were prepared. Specifically, the binder solution was produced by adding 120 g of a solvent-soluble polymer (polyethylene oxide (PEO): molecular weight 100,000 to 200,000, product name "Alkox R-150", manufactured by Meisei Chemical Industry Co., Ltd.) to 3,480 g of water, and mixing at 3,000 rpm for 5 minutes using a high-speed homogenizer (manufactured by Chuo Rika Co., Ltd., LZB14-HM-1) to obtain the binder solution. Next, carbon material granules were manufactured. Specifically, 360 g of CB (Li435, manufactured by Denka Co., Ltd.) and various CNTs pulverized (particle size after pulverization: 40 μm) with a pin mill (DD-2-3.7) manufactured by Seishin Enterprise Co., Ltd. were put into a Lödige mixer (manufactured by Lödige, model M20, volume 20 L), and while stirring at 250 rpm, 3600 g of polymer aqueous solution was sprayed from the upper input hole and mixed for 15 minutes, after which the spraying of the aqueous solution was stopped and the mixture was stirred for 15 minutes to perform particle size adjustment, and a wet carbon material granule was obtained. After that, the mixture was dried with a hot air dryer to obtain a carbon material granule. Example 1: 30% crushed graphitized CNT / 70% crushed CB Comparative Example 1: Graphitized CNT 30% / CB crushed product 70% Comparative Example 2: 30% crushed raw CNT / 70% crushed CB

[0052] (Preparation of resin composition) A resin composition was prepared by blending 2% of each of the CNTs listed below into polypropylene resin (Prime Polymer's "J229E") and mixing the mixture at 210°C and 100 rpm for 4 minutes using a Plastomill.

[0053] [Evaluation of CNTs, carbon material granules, and resin compositions] The properties (ash content, dispersibility, volume resistivity) of the CNTs, the carbon material granules, and the resin composition were evaluated by the following methods. The results are shown in Table 1. (1)Ash content The ash content of the CNT or carbon material granules was measured in accordance with JIS K-6218-2 (ASTM D-1506). Specifically, the sample was placed in a porcelain crucible and completely incinerated at 750°C or 825°C, and the ash content (unit: %) was calculated from the amount of residue. The progress of the graphitization process can be determined from the ash content, and the lower the ash content, the more progressed the graphitization process is. It can also be said that the lower the ash content, the fewer metal impurities there are in the CNT or carbon material granules. (2) Dispersibility The dispersibility of the resin composition was evaluated by melt pressing the resin composition to prepare a thin piece, and observing the thin piece using transmitted light through a microscope (magnifications of 50x and 200x). The degree of dispersion was evaluated in the range of 0 to 10. The higher the value, the better the dispersibility. The photograph of the observation (magnification of 50x) is shown in Figure 2. (3) Volume resistivity Using a Labo Plastomill, three resin compositions were prepared by mixing the carbon material granules in polycarbonate resin (Teijin's "Panlite L-1225WP") at 1.5%, 1.7%, and 2% amounts at 280°C and 100 rpm for 4 minutes. The volume resistivity of the resin composition was then measured.

[0054] [Table 1]

[0055] The results shown in Table 1 reveal the following: In other words, the blended granules of pulverized graphitized CNT and CB (Example 1) had significantly improved dispersibility and volume resistivity compared to the granules of unpulverized graphitized CNT and CB (Comparative Example 1). It was found that, despite the significant reduction in catalytic metals by graphitization, the blended granules of CNT and CB that had not been graphitized (Comparative Example 2) also showed performance in terms of dispersibility and volume resistivity similar to that of the blended granules of CNT and CB that had not been graphitized (Comparative Example 2). From the above, it was confirmed that the carbon material granules according to the present invention can reduce metal impurities and have excellent dispersibility. [Explanation of symbols]

[0056] 1...Screw case, 2...Screw, 3...Extractor blade, 4...Screen, 5...Screen holder.

Claims

1. A method for producing a carbon material granule containing carbon black having a particle size of 500 μm or less as measured by a method described in JIS K-6219-4, carbon nanotubes satisfying either one of the following condition 1 and condition 2, and a water-soluble polymer attached to the carbon black and the carbon nanotubes, comprising the steps of: A step of mixing carbon black having a particle size of 500 μm or less according to the method described in JIS K-6219-4 with carbon nanotubes satisfying either one of the condition 1 and the condition 2 to obtain a mixture; dissolving the water-soluble polymer in water to prepare a binder solution; and adding the binder solution little by little to the mixture, mixing the mixture, and granulating the mixture to obtain a carbon material granule. A method for producing carbon material granules. (Condition 1) Carbon nanotubes that have been subjected to a graphitization treatment and then a crushing treatment, and the particle diameter D of the carbon nanotubes 50 is 100 μm or less. (Condition 2) The carbon nanotubes, which are either powder or granular carbon nanotubes, are subjected to a pulverization process and then graphitized.

2. A method for producing a carbon material granule containing carbon black having a particle size of 500 μm or less as measured by a method described in JIS K-6219-4, carbon nanotubes satisfying either one of the following condition 1 and condition 2, and a water-soluble polymer attached to the carbon black and the carbon nanotubes, comprising the steps of: A step of mixing carbon black having a particle size of 500 μm or less according to the method described in JIS K-6219-4 with carbon nanotubes satisfying either one of the condition 1 and the condition 2 to obtain a mixture; dissolving the water-soluble polymer in water to prepare a binder solution; mixing the mixture with the binder solution to obtain a wet mixture; and granulating the wet mixture to obtain a carbon material granule. A method for producing carbon material granules. (Condition 1) Carbon nanotubes that have been subjected to a graphitization treatment and then a crushing treatment, and the particle diameter D of the carbon nanotubes 50 is 100 μm or less. (Condition 2) The carbon nanotubes, which are either powder or granular carbon nanotubes, are subjected to a pulverization process and then graphitized.

3. A method for producing a carbon material granule according to claim 1 or claim 2, the water-soluble polymer is at least one selected from the group consisting of a polymeric surfactant and a high molecular weight polymer; the surfactant is at least one selected from the group consisting of anionic surfactants, cationic surfactants, nonionic surfactants, and amphoteric surfactants; The polymer is at least one selected from the group consisting of polyethylene oxide, polypropylene glycol, polyvinyl alcohol, polyvinyl acetate, polyvinylpyrrolidone, polyacrylamide, polyethyleneimine, polybutyleneimine, methylcellulose, ethylcellulose, carboxymethylcellulose, hydroxyethylcellulose, hydroxypropylmethylcellulose, oxidized starch, and gelatin; A method for producing carbon material granules.

Citation Information

Patent Citations

  • Carbon nanotube as well as preparation method and application thereof

    CN112750627A

  • Negative electrode material and preparation method and application thereof

    CN114142029A

  • Composite electrode based on carbon nanotube / zirconium hydrogen phosphate and preparation method and application thereof

    CN115991523A

  • Manufacturing process of carbon NANO material-resin composite molding and carbon NANO material-resin composite molding

    JP2007090827A

  • Composite carbon fiber

    JP2014177722A

Cited By

  • Method for producing carbon-material granules

    WO2026163270A1